10p15.3p13 duplication inherited from paternal balance translocation (46, XY, t(5;10)(q35.1;p13)) identified on non‐invasive prenatal testing. Issue 6 (June 2017) - Mei, Jin; Wang, Hao; Zhan, Liyong
Abstract: Balanced reciprocal translocations are relatively common human genetic abnormalities that involve the exchange of the terminal segments between different chromosomes and have an approximately 5–80% chance of generating an embryo with chromosomal abnormalities. Non‐invasive prenatal testing (NIPT) has been increasingly used in clinical practice to detect fetal trisomies 21, 18 and 13 with a sensitivity and specificity of up to 99%. In this report, we describe a duplication on chromosome 10 and a deletion on chromosome 5 that were first detected on NIPT. Multiple follow‐up invasive tests, such as prenatal BACs‐on‐Beads (BoBs), GTG banding and single nucleotide polymorphism (SNP) array, confirmed the NIPT results. Furthermore, GTG banding identified a normal maternal karyotype and a paternal karyotype with a balanced translocation of 46, XY, t(5;10)(q35.1;p13), inherited by the child. Therefore, NIPT could be a new method for the prenatal diagnosis of fetal chromosomal abnormalities, which, in the present study, were confirmed on multiple clinical and molecular methods as being derived from paternal balanced chromosomal rearrangements.